9. Teacher Training in Arts Education in France (Contemporary Challenges in Arts Education) - Apostu Liliana Isabela; Apalaghie Dan (Sciendo, 2022)
Music education or education through music, a means of emancipation of new generations. To what extent can the education of future teachers be directly responsible for the ideals of tomorrow's multicultural society ? This article aims to open up a vision of education, a solution among solutions, based on the development of a curriculum centered around the values of equality and equity, around the principles of freedom and secularism. The intellectual preparation and training of future education professionals is a process of continuous transformation, adaptation and multidisciplinary transversal training, in which the Common Core is the common stem of knowledge and skills needed to educate teachers and students at the same time.